Theoretical and Legal Analysis of the Causes of the Crime and the Conditions Conducive to its Committing - Ne’matov Azizbek G’olibjon o’g’li (Zien Journals, 2022)
The article analyzes the opinions of experts in the field of crime prevention of investigative bodies, their concept, content, as well as normative legal documents in the field of crime prevention of investigative bodies. Investigative bodies pay special attention to the issue of crime prevention. In the concluding part of the article, it is explained that the organization of a new mechanism of preventive activities and its effective planning are of great importance in the early prevention of crimes.
Keywords: Crime prevention; causes and conditions of crime; types; presentation